The Feasibility and Acceptability of a Community Science Approach to Explore Infant Formula Preparation Safety in the Home - Sara Jones; Jonie Cooper; Abbie Dolling; Tara McNamara; Susan Dvorak; Vicky Sibson; Amy Brown; Emma Yhnell; Phyll Buchanan; Sharon Breward; Rebecca Ellis; Aimee Grant (Citizen Science: Theory and Practice)
Parents often seek out information about health and parenting topics, but despite this, there have been few attempts to actively engage them in the research process. We aimed to assess the feasibility and acceptability of using community science (CS) in a pilot study to explore infant formula preparation safety in the home in the United Kingdom. Parents were involved at each research stage, including (i) pre-funding consultation (n = 17), (ii) research design (n = 19), (iii) data generation (n = 151), (iv) research education (n = 8), (v) data analysis (n = 5), (vi) reflections on participation in CS (n = 151) and participation in the data analysis group (n = 5), and (vii) the development of research outputs (n = 5). Parents proposed that a closed Facebook group would be a feasible platform for CS. This had limited effectiveness in engaging parents in research design but was more successful in recruitment to the data generation stage. Many parents reported enjoyment in taking part and feeling valued for their knowledge, although for a minority, increased awareness of the risks of preparing infant formula caused distress. Research education engagement on social media was limited. The small data analysis group allowed for more in-depth contributions; however, facilitation was resource intensive so was necessarily limited. Participant fatigue is a risk in CS. Solutions to ongoing engagement, especially (in our case) with research education, are needed. Researchers must also mitigate harm to community scientists arising from their involvement in investigating sensitive topics. Existing research contexts created barriers, so in practice, more funding is needed to facilitate CS.